P759 Perianal Crohn's disease – therapeutic response and anal cancer risk - a single centre retrospective cohort. (30th January 2023) - Conceição, D; Rajão Saraiva, M; Lemos Garcia, J; Rosa, I; Moleiro, J; Simões, C; Claro, I
Abstract: Background: Perianal manifestations of Crohn's disease (CD) occur in up to 43% of CD patients, and are strongly associated with colonic and rectal involvement. They have negative effects on patients' quality of life and the risk of anal cancer (AC) is two to three times higher than the general population. The management of perianal disease (pCD) often includes a local approach but also a systemic therapeutic escalation. Methods: Aim: to evaluate the response to therapy and the incidence of AC in patients with pCD. Retrospective single-centre study, recruiting all adult patients with pCD. We analysed the population demography, extraintestinal manifestations, the presence of perianal disease at diagnosis, the subtype of pCD, PDAI score, baseline treatment and the need for readjustment. We evaluated the clinical and MRI response atsix months, further therapeutic changes required, the incidence of anal and rectal cancer and the status at last follow-up. Results: 174 patients with CD, 50 with pCD (29%) – from these: 59% Male; Age 22-77 (median 51); Extraintestinal manifestations 16 (31%); pCD at the diagnosis of CD 29 (57%). pCD characterization: fistula 46 (92%) (simple 6; complex 40); abscess 27 (54%); fissure 12 (24%). PDAI score: 1-17 (median 7, 5). Approach: fistulotomy 25 (49%); seton placement 13 (25%); protective stoma 5 (9, 8%). Antibiotics in 43 (86%). Therapeutic change 40 (84%) -started: corticosteroid course 9 (18%) (all with rectal disease activity), anti-TNF 28 (55%), thiopurine 23 (45%) 13 of them in monotherapy. At 6 months: global clinical improvement 41 (81%); healed PD 18 (35%). Follow up 2-49 years (mean 20); Subsequent treatment change during follow up: 28 (55%). At last follow-up: luminal CD in clinical remission 44 (86%); pCD improvement 43 (84%) and deep remission in 32 (64%). By univariate analysis there was no significant association between starting anti-TNF therapy or monotherapy with thiopurine and clinical response at 6 months, or at last follow up, with MRI improvement. During follow up, 3 patients (6%) develop AC (2 perianal fistula-related cancer; 1 adenocarcinoma). There was no significant association with the use of anti-TNF (p 0, 356) or thiopurine (p 0, 312) but there was an association with absence of clinical response at 6 months (p 0, 050) and lack of MRI improvement (p 0, 057). There were no rectal cancer cases. Conclusion: Most patients with pCD required therapeutic changes, the majority of them initiating anti-TNF – this resulted in luminal disease remission and at least pCD improvement in more than 80% of patients. The small sample size limited our results, but AC seemed to be more common in patients with chronically active pCD.